Reversed cyclic loading tests on precast concrete sandwich shear walls under different axial compression ratios. (15th August 2022) - Li, Ya; Xue, Weichen; Yun, Yanchun; Ding, Hong
Abstract: A precast concrete sandwich shear wall (PCSSW) typically consists of an insulation layer separated by two concrete wythes. The insulation layer in this sandwiched structure is well protected and could reach a same life span of the load bearing system. Depending on the configuration of inner concrete wythe, PCSSWs generally fall into two categories: PCSSWs with solid inner wythe and PCSSWs with composite inner wythe. To study the seismic performance of both the two categories of PCSSWs, low-reversed cyclic loading tests under axial compression ratio of 0.12 or 0.3 were performed on six full-scale shear wall specimens, including two PCSSWs with solid inner wythe, two PCSSWs with composite inner wythe and two cast-in-place (CIP) shear walls. Test results revealed that all specimens exhibited flexural-shear failure. All the specimens had plump hysteresis loops and satisfactory energy dissipation performance. Under the same axial compression ratio, the loading capacities of the PCSSW specimens increased by 0.4%–13.8% compared to the CIP specimens. Under the axial compression ratio of 0.12, the displacement ductility of the PCSSW specimens ranged from 3.81 to 4.30, which was 24.7%–15.0% lower than that of the CIP specimen. As for the specimens under the axial compression ratio of 0.3, the displacement ductility of the PCSSW specimen with solid inner wythe and the PCSSW specimen with composite inner wythe was 3.28 and 3.05, respectively, which was similar to that of the CIP specimen with the difference not greater than 5%. Besides, the stiffness degradation of the two types of PCSSWs was found to be comparable to that of the control specimens. Based on the test results, a four-linear degradation restoring force model was proposed. Highlights: Cyclic loading tests on precast concrete sandwich shear walls (PCSSWs) were conducted. The effects of configuration of inner wythe and axial compression ratio were investigated. A four-linear degradation restoring force model for PCSSWs was developed.